(untitled) (Biocenosis, 2014)
The study was conducted in the communities of Rosario, Puerto Humo, Pozo de Agua and Corral de Piedra, adjacent to the western margin of Tempisque river, in order to determine what is the popular perception and knowledge of the inhabitants of these four villages with respect to the presence of crocodiles (C. acutus). 33 surveys were conducted between January and February 2010. The interviewees responded that crocodiles feed on fish (87,87%) and small mammals (72,7%), 81,8% do not know how is the courtship in this species; 57,5% do not know when is their reproductive time. They believe nests are in caves (39,3%), out of water (48,5%) or that are holes (39,3%). The residents of these villages know that the river has crocodiles (75,75%), believe that this population has increased in recent years (93,9%). They also believe that crocodiles are dangerous and a threat to people (87,9%) and that species is not considered endangered (87,9%). In turn, they think that a crocodile can attack anytime and attacks have remained the same for several years (51,5%). They propose that attacks on humans have occurred because they invade the habitat of the animal (48,5%). As a conclusion, the author proposes a process of continuing education in the communities that share ecosystems with wildlife, as this knowledge will be key to their overall development and of the species that coexist with them.